Adolescent choices of walking activities during physical education classes - Corrêa, Umberto Cesar; Silva Filho, Antônio Sabino da (Brazilian journal of physical education and sport, 2008)
The objective of this study was to investigate the adolescent's choices of both genders in relation to walking activities in physical education class. The participants were boys and girls (N = 158) with average age of 14.52 (± 0.75) years, from eighth-grade of the secondary school. The walking activities with different themes (social, play, competition, and exercise/fitness) which could be chosen from two distinct lists, during eight classes. The activities were developed as a part of the curricular physical education program. The dependent variable was the quantity of choices of each activity, on each class. The data were analyzed by nonparametric statistic. The results permitted to conclude that the social walking received more choices by adolescents of both genders than other activities, and that girls chose it more than boys. In relation to intermediate choices could be concluded that girls chose the walking with play more than boys, and that boys chose the walking with competition more than girls. The difference in quantity of choice between boys and girls occurred only in the first and second days.